Justice and the politics of difference - Young, Iris Marion; Allen, Danielle S. (Princeton classic editions, 2022)
"In this classic work of feminist political thought, Iris Marion Young challenges the prevailing reduction of social justice to distributive justice. The starting point for her critique is the experience and concerns of the new social movements that were created by marginal and excluded groups, including women, African Americans, and American Indians, as well as gays and lesbians. Young argues that by assuming a homogeneous public, democratic theorists fail to consider institutional arrangements for including people not culturally identified with white European male norms. Consequently, theorists do not adequately address the problems of an inclusive participatory framework. Basing her vision of the good society on the culturally plural networks of contemporary urban life, Young makes the case that normative theory and public policy should undermine group-based oppression by affirming rather than suppressing social group differences"
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; inégalités; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Hermeneutical Backlash: Trans Youth Panics as Epistemic Injustice - George, B. R.; Goguen, Stacey (Feminist Philosophy Quarterly, 2021)
In this paper we use the contemporary example of trans youth panics to introduce the notion of hermeneutical backlash, in which defenders of an established, unjust hermeneutical regime actively work to undermine and discredit hermeneutical liberation. We argue that the strategies and tropes of the trans youth panic illustrate a general propaganda vulnerability of epistemic liberation movements (including familiar examples from recent history), and so are troubling for reasons that go beyond their application to trans youth. This exploration of a few specific cases of hermeneutical liberation and hermeneutical backlash calls attention to the need for further theoretical work on the dynamics of struggles for (and against) hermeneutical justice.
Keywords: approches et analyses; backlash herméneutique; cours; cycles supérieurs; discipline; discours dominant; discours médiatique; enfants trans*; fem9000; histoire et politique; hétérosexisme; injustices herméneutiques; militance; philosophie; philosophie féministe; sciences humaines; systèmes d'oppressions; thématiques; transphobie; violences

Epistemic Decolonization as Overcoming the Hermeneutical Injustice of Eurocentrism - Posholi, Lerato (Philosophical Papers, 2020)
This paper is broadly concerned with the question of what epistemic decolonization might involve. It is divided into two parts. The first part begins by explaining the specifically epistemic problem to which calls for epistemic decolonization respond. I suggest that calls for decolonization are motivated by a perceived epistemic crisis consisting in the inadequacy of the dominant Eurocentric paradigm to properly theorize our modern world. I then discuss two general proposals, radical and moderate, for what epistemic decolonization might involve. In the second part, I argue that the inadequacy of Eurocentric epistemic resources constitutes a hermeneutical injustice caused by an irreducible form of epistemic oppression. I then argue that addressing this form of epistemic oppression requires thinking ‘outside’ of the Eurocentric paradigm because the paradigm might fail to reveal and address the epistemic oppression sustaining it. This lends further plausibility to the radical proposal that epistemic decolonization must involve thinking from ‘outside’ the Eurocentric paradigm, but also accommodates the moderate proposal that adopting critical perspectives on Eurocentric thought is an important part of epistemic decolonization.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; décolonisation épistémique; fem9000; féminisme décolonial; injustices herméneutiques; injustices épistémiques; philosophie; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences; études décoloniales

On Epistemic Appropriation - Davis, Emmalon (Ethics, 2018)
In this article, I offer an account of an unjust epistemic practice―namely, epistemic appropriation―that harms marginalized knowers through the course of conceptual dissemination and intercommunal uptake. The harm of epistemic appropriation is twofold. First, while epistemic resources developed within the margins gain uptake with dominant audiences, those resources are overtly detached from the marginalized knowers responsible for their production. Second, epistemic resources developed within, but detached from, the margins are utilized in dominant discourses in ways that disproportionately benefit the powerful.
Keywords: approches et analyses; appropriation épistémique; cours; cycles supérieurs; discipline; discours dominant; droits des personnes; fem9000; injustices épistémiques; inégalités; philosophie; privilèges; rapports de pouvoir; savoirs des marges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Epistemic Exploitation - Berenstain, Nora (Ergo, an Open Access Journal of Philosophy, 2016)
Epistemic exploitation occurs when privileged persons compel marginalized persons to educate them about the nature of their oppression. I argue that epistemic exploitation is marked by unrecognized, uncompensated, emotionally taxing, coerced epistemic labor. The coercive and exploitative aspects of the phenomenon are exemplified by the unpaid nature of the educational labor and its associated opportunity costs, the double bind that marginalized persons must navigate when faced with the demand to educate, and the need for additional labor created by the default skepticism of the privileged. I explore the connections between epistemic exploitation and the two varieties of epistemic injustice that Fricker (2007) identifies, testimonial and hermeneutical injustice. I situate epistemic exploitation within Dotson’s (2012; 2014) framework of epistemic oppression, and I address the role that epistemic exploitation plays in maintaining active ignorance and upholding dominant epistemic frameworks.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; exploitation épistémique; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; oppression épistémique; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; travail; violences; éthique

Privilege: Expanding on Marilyn Frye's "Oppression" - Bailey, A. (JOURNAL OF SOCIAL PHILOSOPHY -AUGUSTA-, 1998)
This essay serves as both a response and embellishment of Marilyn Frye's now classic essay " Oppression." It is meant to pick up where this essay left off and to make connections between oppression, as Frye defines it, and the privileges that result from institutional structures. This essay tries to clarify one meaning of privilege that is lost in philosophical discussions of injustice. I develop a distinction between unearned privileges and earned advantages. Clarifying the meaning of privilege as unearned structural advantage makes visible the role white privilege plays in maintaining complex systems of domination such as racism, sexism, heterosexism and classism. Using a critical reading of both Frye and Young's accounts of oppression as a springboard, I develop a definition of privilege as a particular class of unearned advantages. -/- I distinguish my account of privilege from standard legal and philosophical definitions of privilege. The general distinction I make between privileges and advantages rests on three interrelated claims: that benefits granted by privilege are always unearned and conferred systemically to members of dominant social groups; that privileges granted to members of dominant groups solely on the basis of their membership in these groups is never justifiable; and, that privileges have an unconditional value that can be explained not only in terms of immunities, but also in terms of additional benefits
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; justice sociale; phi4336; philosophie; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis